Human capital and the phenomenon of increasing returns in economic growth models - Mayilyan, Firuza (Bulletin of Yerevan University G: Economics, 2025)
The paper investigates the historical preconditions underlying the emergence of the concept of the principle of diminishing returns to factors of production. An analysis of the manifestation of this principle in the scope of all factors of production is carried out. In light of the analysis of the characteristics of human capital, an approach has been proposed in which the principle of diminishing marginal returns is not applicable to investments in human capital at the macroeconomic level in the long run. Human capital generates increasing returns on investment while alleviating the impact of diminishing returns on other factors of production. In general, while accepting the principle of diminishing returns to factors of production, it should be noted that the mechanical extension of this principle to all types of economic activity is not scientifically justified. There are certain types of activities and economic sectors to which, in our opinion, this law does not apply. Moreover, these types of activities hinder the manifestation of the principle of diminishing returns to other factors of production. In particular, it is known that increased investment leads to diminishing returns on investment. However, this pattern applies to investment in physical capital. In our opinion, this pattern does not apply to investment in human capital. Moreover, investment in human capital is presumably expected to provide increasing returns. However, it should be emphasized that this approach lacks a clear system of evidence and is based on empirical observations. Furthermore, the principle of increasing returns to investment in human capital has a long-term lag in its impact on economic variables and manifests itself in the long term and primarily at the macro level.